On the evaluation of economic mobility - Peter Gottschalk; Enrico Spolaore (Brown University, Department of Economics, 2001)
This paper presents a framework for the evaluation and measurement of reversal and origin independence as separate aspects of economic mobility. We show how that evaluation depends on aversion to multi-period inequality, aversion to inter-temporal fluctuations, and aversion to future risk. We construct extended Atkinson indices that allow us to quantify the relative impact of reversal and origin independence on welfare. We apply our approach to the comparison of income mobility in Germany and in the United States. When aversion to inequality is the only consideration, the US gains more from mobility than Germany. This reflects similar gains from reversal in the two countries but greater gains in the US from origin independence. The introduction of aversion to intertemporal fluctuations and aversion to future risk makes the impact of mobility in the two countries more similar. – Mobility ; Reversal ; Origin Independence ; Time Independence ; Welfare
Keywords: D60; D63; J60; J69; 330; Soziale Mobilität; Einkommensverteilung; Soziale Wohlfahrtsfunktion; Theorie